2018
DOI: 10.1111/mpp.12742
|View full text |Cite
|
Sign up to set email alerts
|

Redox signalling from NADPH oxidase targets metabolic enzymes and developmental proteins in Fusarium graminearum

Abstract: NADPH oxidase (NOX) is one of the sources of reactive oxygen species (ROS) that modulates the activity of proteins through modifications of their cysteine residues. In a previous study, we demonstrated the importance of NOX in both the development and pathogenicity of the phytopathogen Fusarium graminearum. In this article, comparative proteomics between the wild-type and a Nox mutant of F. graminearum was used to identify active cysteine residues on candidate redox-sensing proteins. A two-dimensional gel appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
0
7
0
1
Order By: Relevance
“…Moreover, only 30 FHB-regulated wheat proteins displayed abundance changes driven at least in part by the strain genetics (i.e., Cv × T{S}_effect proteins). The additional power provided by the integrative analysis of both the host and the pathogen datasets identified covariance patterns between 13 wheat Cv × T{S}_effect proteins and 10 putative F. graminearum effectors, among which five were previously described to be involved in fungal virulence: FG001_05235, FG001_07686, FG001_07526, FG001_00183, and FG001_10559 (Markham and Collinge, 1987;Voigt et al, 2005;Niu et al, 2013;Son et al, 2013;Blümke et al, 2014;Qin et al, 2015;Yao et al, 2016;Furukawa et al, 2017;Brauer et al, 2019a;Fernando et al, 2019). Four of these fungal proteins exhibited abundance changes explained only by the F. graminearum genetic backgrounds, with a maximal abundance detected in the samples inoculated with the most aggressive strain, MDC_Fg1 (Fabre et al, 2019a).…”
Section: Marginal Proteome Regulations Discriminate Wheat Cultivars Of Contrasting Fhb Susceptibilitiesmentioning
confidence: 99%
“…Moreover, only 30 FHB-regulated wheat proteins displayed abundance changes driven at least in part by the strain genetics (i.e., Cv × T{S}_effect proteins). The additional power provided by the integrative analysis of both the host and the pathogen datasets identified covariance patterns between 13 wheat Cv × T{S}_effect proteins and 10 putative F. graminearum effectors, among which five were previously described to be involved in fungal virulence: FG001_05235, FG001_07686, FG001_07526, FG001_00183, and FG001_10559 (Markham and Collinge, 1987;Voigt et al, 2005;Niu et al, 2013;Son et al, 2013;Blümke et al, 2014;Qin et al, 2015;Yao et al, 2016;Furukawa et al, 2017;Brauer et al, 2019a;Fernando et al, 2019). Four of these fungal proteins exhibited abundance changes explained only by the F. graminearum genetic backgrounds, with a maximal abundance detected in the samples inoculated with the most aggressive strain, MDC_Fg1 (Fabre et al, 2019a).…”
Section: Marginal Proteome Regulations Discriminate Wheat Cultivars Of Contrasting Fhb Susceptibilitiesmentioning
confidence: 99%
“…Fernando et al (2019) identified 118 redox‐modified proteins in F . graminearum by comparing the wild‐type strain and the NoxA / NoxB gene disruption mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, GPI-anchored domains were present in the predicted protein products of the FGSG02022 and FGSG10089 genes.The FGSG02022 gene encodes β-(1→3) glucanosyltransferase and FGSG10089 is a homologue of ECM33 involving sporulation in Saccharomyces cerevisiae and Aspergillus fumigatus (Chabane et al, 2006;Pardo et al, 2004). The FGSG02022 gene could not be disrupted in F. graminearum, possibly because it is essential for survival, whereas FGSG10089 gene disruption reduces the pathogenicity of F. graminearum without producing any changes in growth or 15-acetyl DON production (Fernando et al, 2019). The FGSG02810 gene, encoding a putative GPI-anchored protein, was identified as a pathogenicity gene in F. asiaticum (Suga et al, 2016), although its function is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative transcriptomics and experimental evidence in other fungal studies revealed that transporter genes were involved in different levels of sensitivity to fungicide treatment [20,21]. Proteomics has also been frequently employed in research on F. graminearum, especially in the discovery of virulence factors and in gene function studies [22][23][24][25]. However, there are only a few reports about the influence of fungicide treatment on the proteome of F. graminearum [19,26].…”
Section: Introductionmentioning
confidence: 99%